Application of AI in the identification of gastrointestinal stromal tumors: a comprehensive analysis based on pathological, radiological, and genetic variation features - Zheng, Lei; Jin, Dan-Wen; Yu, Hong-Wei; Yu, Ze; Qian, Li-Yong (Frontiers in Genetics, 2025)
Gastrointestinal stromal tumors (GISTs) are uncommon tumors that arise from the gastrointestinal tract, making their early diagnosis and precise identification essential for the effective clinical management. Recently, the use of artificial intelligence (AI) technologies in medicine has grown significantly, showcasing remarkable potential, especially in analyzing the pathological images, radiological features, and genetic variations. This work compiles the most recent research on the application of AI in detecting and identifying GISTs, focusing on its role in pathological image analysis, the extraction of radiological characteristics, and the interpretation of genomic data. By offering a thorough overview of these advancements, this article aims to provide a valuable reference for future research and clinical practices related to the diagnosis and treatment of GISTs.